Concentration-driven reverse membrane bioreactor for the fermentation of highly inhibitory lignocellulosic hydrolysate. (May 2020) - Mahboubi, Amir; Elyasi, Shilan; Doyen, Wim; De Wever, Heleen; Taherzadeh, Mohammad J.
Graphical abstract: Highlights: Reverse membrane bioreactor was used for fermentation of wheat straw hydrolysate. Diffusion cell was used to measure the diffusion rate of medium compounds through the membrane. Membrane-confined yeast cells could detoxify a medium containing up to 16 g/l furfural. High sugar co-utilization and ethanol yield was achieved in rMBR up to 9 g/l of initial furfural. The inhibitor tolerance threshold was reached in rMBR with high furfural to cell ratio of 9.5:1. Abstract: Optimal production of lignocellulosic bioethanol is hindered due to commonly faced issues with the presence of inhibitory compounds and sequentially consumed sugars in the lignocellulosic hydrolysate. Therefore, in order to find a robust fermentation approach, this study aimed at enhancing simultaneous co-assimilation of sugars, and inhibitor tolerance and detoxification. Therefore, fermentation of toxic wheat straw hydrolysate containing up to 20 g/l furfural, using the concentration-driven diffusion-based technique of reverse membrane bioreactor (rMBR) was studied. The rMBR fermentation of the hydrolysate led to complete furfural detoxification and the conversion of 87 % of sugars into ethanol at a yield of 0.48 g/g. Moreover, when the toxicity level of the hydrolysate was increased to 9 g/l of initial furfural, the system responded exceptionally by reducing 89 % of the inhibitor while only experiencing about 25 % drop in the ethanol yield. In addition, using this diffusion-based set-up in extremely inhibitory conditions (16 g/l furfural), cells could detoxify 40 % of the furfural at a high initial furfural to cell ratio of 9.5:1. The rMBR set-up applied proved that by properly synchronizing the medium condition, membrane area, and inhibitor to cell ratio, some of the shortcomings with conventional lignocellulosic fermentation can be tackled, guaranteeing a robust fermentation.